Assessing the impact of climate change and other factors on yield of cacao (Theobroma cacao L.) in Tagum City, Davao del Norte - Medrano, Lindsay Mae B.; Gomez, Aurelia Luzviminda V. (2018)
The impact of climate change to the world has been more evident than ever. The phenomenon has affected agricultural sector the most, thus also affecting livelihood of many people in developing countries such as the Philippines. Country?s cacao industry is still in the early stage of development, and thus, it is important to assess how the industry is affected by climate change ? this is the main objective of this thesis. Specially, the study aims to assess the impact socio-demographic factors, production inputs, climate change awareness and perception, and the adaptation practices on cacao yield. Primary data were gathered from 109 cacao farmers in Tagum City, Davao del Norte. There were three sets of data gathered during the survey, for years 2012, 2015, and 2017. Data on temperature and rainfall were gathered from PAGASA-USEP Sub-station. Data were analyzed using Tobit regression on GRETL software. Results of the study show that number of seedlings used and farmers? awareness of climate change had statistically significant positive effect on yield for all three years. On the other hand, household size, farmers? access to climate information, replanting/changing to new varieties, transition to organic farming, and increase use of fertilizer as adaptation practices had statistically significant negative effect on yield. Results further show that there was statistically significant difference in the average annual rainfall and average annual temperature during the study period. Results of the study indicate that climate change affected corn yield of the farmers in Tagum City. Improving the knowledge of farmers in proper utilization of inputs and application of adaptation practices is highly recommended. It is also necessary for farmers to have proper access to climate information.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2018